2015
DOI: 10.1111/ddg.12836
|View full text |Cite
|
Sign up to set email alerts
|

Multiple miliary osteoma cutis of the scalp

Abstract: Sehr geehrter Herausgeber, wir berichten über den Fall eines 76-jährigen Patienten, der sich aufgrund größenprogredienter, asymptomatischer, seit mehr als sieben Jahren bestehender Läsionen am Capillitium vorstellte. Im Vorjahr unterzog sich der Patient aufgrund multipler aktinischer Keratosen einer Lokaltherapie mit Diclofenac (Solaraze ® ), der sich im Verlauf eine photodynamische Therapie anschloss. Vormals bestehende Hauterkrankungen oder Traumen im Bereich des Capillitiums werden verneint.Bei der klinisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Eun Joo Jang et al suggested that MICC can resemble warts, epidermal cysts, molluscum contagiosum, and syringomas [ 9 ] . In our case, we found a clinical resemblance to multiple miliary osteoma cutis, in which histology shows extraskeletal bone formation in the skin and/or subcutis [ 10,11 ] .…”
Section: Milia-like Calcinosis Cutismentioning
confidence: 67%
“…Eun Joo Jang et al suggested that MICC can resemble warts, epidermal cysts, molluscum contagiosum, and syringomas [ 9 ] . In our case, we found a clinical resemblance to multiple miliary osteoma cutis, in which histology shows extraskeletal bone formation in the skin and/or subcutis [ 10,11 ] .…”
Section: Milia-like Calcinosis Cutismentioning
confidence: 67%
“…Literature reports two cases of primary MMOC of the scalp (5,9) and one case of MMOC secondary to folliculitis decalvans (10). To our knowledge, this is the first reported case of OC originating from a previous LPP.…”
Section: A Case Of Secondary Osteoma Cutis Associated With Lichen Plamentioning
confidence: 78%
“…It has been hypothesized that osteomas are secondary to dystr ophic changes in acne scars. Location on the scalp [7] is uncommon, and appears mainly in males.…”
Section: Discussionmentioning
confidence: 99%